Chloride stress triggers maturation and negatively affects the postharvest quality of persimmon fruit. Involvement of calyx ethylene production - Besada, Cristina; Gil, Rebeca; Bonet, Luis; Quinones, Ana; Intrigliolo, Diego S. (Elsevier, 2020)
In recent years many hectares planted with persimmon trees in E Spain have been diagnosed with chloride toxicity. An effect of this abiotic stress on fruit quality has been reported in different crops. However, the impact of chloride stress on persimmon fruit quality is unknown. The harvest and postharvest quality of persimmons harvested from trees that manifest different intensities of chloride toxicity foliar symptoms was evaluated herein. Our results revealed that fruits from trees under chloride stress conditions underwent chloride accumulation in the calyx, which was more marked the greater the salt stress intensity trees were exposed to. Increased chloride concentrations in the calyx stimulated ethylene production in this tissue. In the fruits affected by slight and moderate chloride stress, calyx ethylene production accelerated the maturity process, as reflected by increased fruit colour and diminished fruit firmness. In the fruits under severe chloride stress, the high ethylene levels in the calyx triggered autocatalytic ethylene production in other fruit tissues, which led fruit maturity to drastically advance. In these fruits effectiveness of CO2 deastringency treatment was not complete and fruit softening enhanced during the postharvest period. Moreover, chloride stress conditions had a marked effect on reducing fruit weight, even in slightly stressed trees.